Production of Manganese Peroxidase and Organic Acids and Mineralization of (14)C-Labelled Lignin ((14)C-DHP) during Solid-State Fermentation of Wheat Straw with the White Rot Fungus Nematoloma frowardii - Hofrichter, Martin (American Society for Microbiology, 1999)
The basidiomycetous fungus Nematoloma frowardii produced manganese peroxidase (MnP) as the predominant ligninolytic enzyme during solid-state fermentation (SSF) of wheat straw. The purified enzyme had a molecular mass of 50 kDa and an isoelectric point of 3.2. In addition to MnP, low levels of laccase and lignin peroxidase were detected. Synthetic (14)C-ring-labelled lignin ((14)C-DHP) was efficiently degraded during SSF. Approximately 75% of the initial radioactivity was released as (14)CO(2), while only 6% was associated with the residual straw material, including the well-developed fungal biomass. On the basis of this finding we concluded that at least partial extracellular mineralization of lignin may have occurred. This conclusion was supported by the fact that we detected high levels of organic acids in the fermented straw (the maximum concentrations in the water phases of the straw cultures were 45 mM malate, 3.5 mM fumarate, and 10 mM oxalate), which rendered MnP effective and therefore made partial direct mineralization of lignin possible. Experiments performed in a cell-free system, which simulated the conditions in the straw cultures, revealed that MnP in fact converted part of the (14)C-DHP to (14)CO(2) (which accounted for up to 8% of the initial radioactivity added) and (14)C-labelled water-soluble products (which accounted for 43% of the initial radioactivity) in the presence of natural levels of organic acids (30 mM malate, 5 mM fumarate).